Green high-strength foamed gypsum and preparation method thereof
By adding specific raw materials to the foamed gypsum and performing irradiation treatment and ultrasonic dispersion, a dense colloidal structure and a uniform foam structure are formed, which solves the shortcomings of existing inorganic insulation materials in thermal conductivity, fire and heat insulation, anti-aging performance and construction convenience, and achieves high strength, low thermal conductivity, good fire and heat insulation performance and freeze-thaw resistance.
Patent Information
- Application Number
- CN202510315327.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-18
AI Technical Summary
The existing inorganic insulation materials have shortcomings in thermal conductivity, fire resistance and thermal insulation properties, anti-aging properties and construction convenience, and are prone to causing wall cracking and alkali reflux.
A green high-strength foamed gypsum is used, and its raw materials include gypsum, cement, nanowhiskers, tourmaline powder, sulfonated flame-retardant mesoporous silicon, graphene oxide, acrylamide and chemical foaming agents. Through technical means such as irradiation treatment and ultrasonic dispersion, a dense colloidal structure and a uniform foam structure are formed.
It achieves high strength, low thermal conductivity, good fire insulation and freeze-thaw resistance, while reducing drying shrinkage and permeability, improving the overall performance of the material and construction convenience.
Smart Images

Figure CN119841613A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foamed gypsum, and in particular to green high-strength foamed gypsum and a preparation method thereof. Background Art
[0002] With the progress of urbanization and urban construction in my country, building energy consumption has increased rapidly. According to statistics, building energy consumption in my country accounts for 30% of the total energy consumption of all types of society. In the context of energy shortage worldwide, building energy conservation has become a major issue of common concern to countries around the world.
[0003] At present, the construction industry has achieved unprecedented rapid development. The implementation of building energy-saving policies has promoted the development of wall insulation materials. Foam plastics and other organic insulation materials are widely used in wall materials, but their poor fire resistance and anti-aging performance and large deformation coefficient have restricted the faster development of this insulation material. Compared with organic insulation materials such as foam plastics, inorganic insulation materials have the advantages of good fire resistance, strong flame retardancy, small deformation coefficient and strong anti-aging performance.
[0004] At present, the main inorganic thermal insulation material is cement-based vitrified microsphere inorganic thermal insulation mortar. The dry density of this mortar is large, basically 400-600kg / m 3 The thermal conductivity is basically between 0.080-0.120W / (m·K). The drying shrinkage rate is large, which can easily cause wall cracks, and it is very easy to produce alkali return in humid areas, affecting the appearance and thermal insulation effect.
[0005] Gypsum building materials are formed by foaming, forming a large number of closed and tiny bubbles inside, which can greatly reduce the thermal conductivity, thus having thermal insulation and heat preservation properties. The ventilation foaming process in current technology is easy to operate, but it is difficult to control the amount of gas in the gypsum mixed slurry, resulting in different sizes and distributions of pores inside the gypsum mold, which is very easy to crack during the gelation and drying process at room temperature, and has poor fireproof and heat insulation effects; and the use of protein foaming agents is limited in material sources and has a short shelf life, which restricts large-scale promotion and application in industrial production.
[0006] At the same time, the existing gypsum insulation materials also have the defects of high permeability absorption, and the strength loss is too high after repeated freezing and thawing. Therefore, it is of great practical significance to study and explore a lightweight, high-strength, fireproof and heat-insulating green foamed gypsum. Summary of the invention
[0007] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a green high-strength foamed gypsum and a preparation method thereof.
[0008] A green high-strength foamed gypsum, the raw materials of which include, by mass, 30-60 parts of gypsum, 5-15 parts of cement, 1-2 parts of nano whiskers, 1-2 parts of tourmaline powder, 4-10 parts of sulfonated flame-retardant mesoporous silicon, 1-5 parts of graphene oxide, 1-2 parts of acrylamide, 0.01-0.1 parts of potassium permanganate, 1-2 parts of water reducer, 1-2 parts of retarder, 1-2 parts of thickener, 1-2 parts of foam stabilizer and 1-3 parts of chemical foaming agent; the sulfonated flame-retardant mesoporous silicon adopts fatty alcohol polyoxyethylene ether as a mesoporous template, takes tetraethyl orthosilicate as a precursor and is compounded with aluminum dihydrogen phosphate, and then is subjected to sulfonation treatment to obtain the sulfonated flame-retardant mesoporous silicon.
[0009] Preferably, the gypsum is desulfurized gypsum.
[0010] Preferably, the cement is PO52.5 Portland cement.
[0011] Preferably, the nano whisker is at least one of nano zinc oxide, nano tin oxide, and nano zinc hydroxystannate.
[0012] Preferably, the water reducer is a naphthalene-based water reducer or a polycarboxylate water reducer.
[0013] Preferably, the thickener is hydroxypropyl methylcellulose and / or polyvinyl alcohol.
[0014] Preferably, the chemical blowing agent is an aqueous solution of hydrogen peroxide.
[0015] Preferably, the sulfonated flame-retardant mesoporous silicon is prepared by the following specific operation: add fatty alcohol polyoxyethylene ether to water and stir evenly, add tetraethyl orthosilicate and aluminum dihydrogen phosphate thereto, stir at 40-50°C for 5-10 minutes, adjust the pH value of the system to 8-9, stir for 5-10 hours, add 4-ethylbenzenesulfonic acid, stir at 150-160°C for 1-2 hours, cool to 40-60°C, filter, wash the filter cake, and vacuum dry.
[0016] Preferably, the mass ratio of fatty alcohol polyoxyethylene ether, ethyl orthosilicate, aluminum dihydrogen phosphate and 4-ethylbenzenesulfonic acid is 1-3:2-4:1-2:0.1-1.
[0017] The preparation method of the green high-strength foamed gypsum comprises the following steps: S1. Stirring sulfonated flame-retardant mesoporous silica with gypsum, cement, nano whiskers, tourmaline powder and foam stabilizer for 1-3 minutes to obtain a premix; S2, adding graphene oxide to water, ultrasonically dispersing for 5-10 minutes, adding acrylamide and continuing ultrasonication for 5-10 minutes, purging with nitrogen for 5-10 minutes, sealing and irradiating with cobalt-60, the irradiation dose is 20-30 kGy, filtering, washing with water, and vacuum drying; then adding water reducer, retarder, thickener, and potassium permanganate to water and stirring for 1-3 minutes to obtain a composite admixture; S3. Add the composite admixture to the premix and stir for 1-3 minutes. Add the chemical foaming agent and continue stirring for 5-10 seconds. Pour, foam, and mold for 2-4 hours before demoulding and curing.
[0018] Preferably, in S2, the ultrasonic frequency is 5-10 kHz.
[0019] Preferably, in S2, the irradiation dose rate is 2.9-3.0 kGy / h.
[0020] Beneficial effects: 1. The present invention is irradiated to graft acrylamide onto graphene oxide, making it have amphiphilic properties, which can effectively promote the uniform dispersion of additives such as water reducer, retarder, thickener, potassium permanganate, etc. into the premix, thereby improving the performance of the gypsum board.
[0021] 2. The present invention uses fatty alcohol polyoxyethylene ether as a mesoporous template, tetraethyl orthosilicate as a precursor, and is compounded with aluminum dihydrogen phosphate to obtain a flame-retardant mesoporous silicon material, which can effectively improve the heat resistance and flame retardancy. The surface is then sulfonated and can be combined with the surface amino groups of the grafted graphene oxide in the composite admixture to form a dense body of a gel structure, thereby improving the flexural strength of the system, reducing shrinkage, and preventing structural cracking; at the same time, a three-dimensional cross-linking effect is generated, and together with fine gypsum particles, a dense colloidal structure is formed, which is not only high in strength, but also can effectively block water infiltration, and at the same time has excellent freeze-thaw resistance, that is, the freeze-thaw cycle has no effect on its anti-seepage properties.
[0022] 3. The grafted graphene oxide of the present invention is combined with nano whiskers to effectively promote the uniform dispersion of chemical foaming agents in the system and promote the foaming of gypsum, which can not only produce fine foam, promote the stable generation of foam, and form a uniform gypsum board, but also increase the early hydration rate and enhance the strength of the hardened body. In combination with the effect of tourmaline powder, the radiation protection performance is better.
[0023] 4. The present invention is green and environmentally friendly, ensuring that the gypsum board has fireproof, heat-insulating and radiation-proof properties. Different building materials can be deployed according to needs. Its hardness meets the highest requirements for exterior wall materials and can withstand at least 9 freeze-thaw cycles. The material can be physically ground into powder and recycled, greatly reducing the cost investment. The present invention improves the overall performance of the gypsum board, is easy to construct and cast, and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a comparison chart of the bulk density and noise reduction coefficient of the foamed gypsum obtained in Example 5 and Comparative Examples 1-2.
[0025] Figure 2 It is a comparison chart of the compressive strength and flexural strength of the foamed gypsum obtained in Example 5 and Comparative Examples 1-2.
[0026] Figure 3 It is a comparison chart of thermal conductivity and drying shrinkage of the foamed gypsum obtained in Example 5 and Comparative Examples 1-2.
[0027] Figure 4 The graph is a change in permeability coefficient of the foamed gypsum obtained in Example 5 and Comparative Examples 1-2 after different freeze-thaw times. DETAILED DESCRIPTION
[0028] The present invention will be further explained below in conjunction with specific embodiments.
[0029] The foam stabilizer used below is cement foam stabilizer (DX-550), purchased from Guangzhou Dongxing Fine Chemical Co., Ltd. The naphthalene-based water reducer used below is purchased from Shandong Wanshan Chemical Co., Ltd. (specification: FDN-C). The polycarboxylate water reducer used below is Sika polycarboxylate water reducer 540P, purchased from Shanghai Hengchuang Chemical Co., Ltd.
[0030] Example 1 A green high-strength foamed gypsum, whose raw materials include: 30kg of desulfurized gypsum, 5kg of PO52.5 silicate cement, 1kg of nano zinc oxide whisker, 1kg of tourmaline powder, 4kg of sulfonated flame-retardant mesoporous silicon, 1kg of graphene oxide, 1kg of acrylamide, 0.01kg of potassium permanganate, 1kg of naphthalene series water reducer, 1kg of sodium gluconate, 1kg of hydroxypropyl methylcellulose, 1kg of foam stabilizer, and 1kg of 28% by mass hydrogen peroxide aqueous solution.
[0031] Sulfonated flame-retardant mesoporous silica was prepared by the following specific operation: 1 kg AEO-9 was added to 20 kg water and stirred evenly, 2 kg ethyl orthosilicate and 1 kg aluminum dihydrogen phosphate were added thereto, and the mixture was stirred at a speed of 100 r / min for 5 min, and the stirring temperature was 40°C. Ammonia water with a mass fraction of 5% was used to adjust the pH value of the system to 8-9, and the mixture was stirred for 5 h. 0.1 kg 4-ethylbenzenesulfonic acid was added, and the mixture was stirred at a temperature of 150°C for 1 h, and the stirring pressure was 0.5 MPa. The mixture was cooled to 40°C, filtered, the filter cake was washed, and vacuum dried.
[0032] The preparation method of the green high-strength foamed gypsum comprises the following steps: S1. Mix sulfonated flame-retardant mesoporous silica with desulfurized gypsum, PO52.5 silicate cement, nano zinc oxide whiskers, tourmaline powder and foam stabilizer, and stir at a speed of 100 r / min for 1 min to obtain a premix; S2, graphene oxide is added to 5kg water, ultrasonically dispersed for 5min, the ultrasonic frequency is 5kHz, acrylamide is added, ultrasonication is continued for 5min, nitrogen purge is carried out for 5min, and the irradiation is sealed and sent to the cobalt-60 irradiation chamber for irradiation, the irradiation dose is 20kGy, and the irradiation dose rate is 2.9kGy / h, filtered, washed once with deionized water, and vacuum dried; then added to 30kg water with naphthalene-based water reducer, sodium gluconate, hydroxypropyl methylcellulose, and potassium permanganate, and stirred at a speed of 100r / min for 1min to obtain a composite admixture; S3. Add the composite admixture to the premix, stir at a speed of 100r / min for 1min, add the hydrogen peroxide aqueous solution, continue stirring for 5s, pour into the mold for foaming, demould after molding for 2h, and cure.
[0033] Example 2 A green high-strength foamed gypsum, whose raw materials include: 60kg of desulfurized gypsum, 15kg of PO52.5 silicate cement, 2kg of nano tin oxide whisker, 2kg of tourmaline powder, 10kg of sulfonated flame-retardant mesoporous silicon, 5kg of graphene oxide, 2kg of acrylamide, 0.1kg of potassium permanganate, 2kg of naphthalene series water reducer, 2kg of sodium gluconate, 2kg of polyvinyl alcohol, 2kg of foam stabilizer, and 3kg of 32% by mass aqueous hydrogen peroxide solution.
[0034] Sulfonated flame-retardant mesoporous silica was prepared by the following specific operation: 3kg AEO-9 was added to 40kg water and stirred evenly, 4kg ethyl orthosilicate and 2kg aluminum dihydrogen phosphate were added thereto, and the mixture was stirred at a speed of 500r / min for 10min, and the stirring temperature was 50°C. Ammonia water with a mass fraction of 10% was used to adjust the pH value of the system to 8-9, and the mixture was stirred for 10h. 1kg 4-ethylbenzenesulfonic acid was added, and the mixture was stirred at a temperature of 160°C for 2h, and the stirring pressure was 0.8MPa. The mixture was cooled to 60°C, filtered, the filter cake was washed, and vacuum dried.
[0035] The preparation method of the green high-strength foamed gypsum comprises the following steps: S1. Mix sulfonated flame-retardant mesoporous silica with desulfurized gypsum, PO52.5 silicate cement, nano-tin oxide whiskers, tourmaline powder and foam stabilizer, and stir at a speed of 200 r / min for 3 min to obtain a premix; S2, graphene oxide is added to 15kg water, ultrasonically dispersed for 10min, the ultrasonic frequency is 10kHz, acrylamide is added, the ultrasound is continued for 10min, nitrogen is purged for 10min, and the irradiation is sealed and sent to the cobalt-60 irradiation chamber for irradiation, the irradiation dose is 30kGy, and the irradiation dose rate is 3kGy / h, filtered, washed 3 times with deionized water, and vacuum dried; then added to 50kg water with naphthalene-based water reducer, sodium gluconate, polyvinyl alcohol, and potassium permanganate, and stirred at a speed of 200r / min for 3min to obtain a composite admixture; S3. Add the composite admixture to the premix, stir at a speed of 200r / min for 3min, add the hydrogen peroxide aqueous solution, continue stirring for 10s, pour into the mold for foaming, demould after molding for 4h, and cure.
[0036] Example 3 A green high-strength foamed gypsum, whose raw materials include: 40kg of desulfurized gypsum, 12kg of PO52.5 silicate cement, 1.3kg of nano tin oxide whisker, 1.8kg of tourmaline powder, 6kg of sulfonated flame-retardant mesoporous silicon, 4kg of graphene oxide, 1.3kg of acrylamide, 0.08kg of potassium permanganate, 1.3kg of polycarboxylic acid water reducer, 1.8kg of sodium gluconate, 1.3kg of hydroxypropyl methylcellulose, 1.8kg of foam stabilizer, and 2.5kg of 29% by mass aqueous hydrogen peroxide solution.
[0037] Sulfonated flame-retardant mesoporous silica was prepared by the following specific operation: 1.5 kg AEO-9 was added to 35 kg water and stirred evenly, 2.5 kg ethyl orthosilicate and 1.8 kg aluminum dihydrogen phosphate were added thereto, stirred at a speed of 200 r / min for 8 min, the stirring temperature was 43 ° C, the pH value of the system was adjusted to 8-9 with 8% ammonia water by mass, stirred for 7 h, 0.7 kg 4-ethylbenzenesulfonic acid was added, stirred at a temperature of 152 ° C for 100 min, the stirring pressure was 0.6 MPa, the temperature was lowered to 55 ° C, filtered, the filter cake was washed, and vacuum dried.
[0038] The preparation method of the green high-strength foamed gypsum comprises the following steps: S1. Mix sulfonated flame-retardant mesoporous silica with desulfurized gypsum, PO52.5 silicate cement, nano-tin oxide whiskers, tourmaline powder and foam stabilizer, and stir at a speed of 150 r / min for 2 min to obtain a premix; S2, adding graphene oxide to 10kg water, ultrasonically dispersing for 7min, the ultrasonic frequency is 9kHz, adding acrylamide, continuing ultrasonication for 6min, nitrogen purging for 9min, sealing and sending to the cobalt-60 irradiation chamber for irradiation, the irradiation dose is 22kGy, the irradiation dose rate is 2.94kGy / h, filtering, washing with deionized water twice, and vacuum drying; then adding to 40kg water with polycarboxylate water reducer, sodium gluconate, hydroxypropyl methylcellulose, and potassium permanganate, stirring at a speed of 150r / min for 2min, to obtain a composite admixture; S3. Add the composite admixture to the premix, stir at a speed of 150r / min for 2min, add the hydrogen peroxide aqueous solution, continue stirring for 9s, pour into the mold for foaming, demould after molding for 2.5h, and cure.
[0039] Example 4 A green high-strength foamed gypsum, whose raw materials include: 50kg of desulfurized gypsum, 8kg of PO52.5 silicate cement, 1.7kg of nano-hydroxy zinc stannate whisker, 1.2kg of tourmaline powder, 8kg of sulfonated flame-retardant mesoporous silicon, 2kg of graphene oxide, 1.7kg of acrylamide, 0.02kg of potassium permanganate, 1.7kg of polycarboxylic acid water reducer, 1.2kg of sodium gluconate, 1.7kg of hydroxypropyl methylcellulose, 1.4kg of foam stabilizer, and 1.5kg of 31% by mass aqueous hydrogen peroxide solution.
[0040] Sulfonated flame-retardant mesoporous silica was prepared by the following specific operation: 2.5 kg AEO-9 was added to 25 kg water and stirred evenly, 3.5 kg ethyl orthosilicate and 1.2 kg aluminum dihydrogen phosphate were added thereto, stirred at a speed of 400 r / min for 6 min, the stirring temperature was 47°C, the pH value of the system was adjusted to 8-9 with 6% ammonia water by mass, stirred for 9 h, 0.3 kg 4-ethylbenzenesulfonic acid was added, stirred at a temperature of 158°C for 80 min, the stirring pressure was 0.7 MPa, the temperature was lowered to 45°C, filtered, the filter cake was washed, and vacuum dried.
[0041] The preparation method of the green high-strength foamed gypsum comprises the following steps: S1, sulfonated flame retardant mesoporous silica is mixed with desulfurized gypsum, PO52.5 silicate cement, nano-hydroxy zinc stannate whisker, tourmaline powder, and foam stabilizer, and stirred at a speed of 150 r / min for 2 min to obtain a premix; S2, adding graphene oxide to 10kg water, ultrasonically dispersing for 9min, the ultrasonic frequency is 7kHz, adding acrylamide, continuing ultrasonication for 8min, nitrogen purging for 7min, sealing and sending to the cobalt-60 irradiation chamber for irradiation, the irradiation dose is 28kGy, the irradiation dose rate is 2.94kGy / h, filtering, washing with deionized water twice, and vacuum drying; then adding to 40kg water with polycarboxylate water reducer, sodium gluconate, hydroxypropyl methylcellulose, and potassium permanganate, stirring at a speed of 150r / min for 2min, to obtain a composite admixture; S3. Add the composite admixture to the premix, stir at a speed of 150r / min for 2min, add the hydrogen peroxide aqueous solution, continue stirring for 7s, pour into the mold for foaming, demould after molding for 3.5h, and cure.
[0042] Example 5 A green high-strength foamed gypsum, whose raw materials include: 45kg of desulfurized gypsum, 10kg of PO52.5 silicate cement, 1.5kg of nano zinc oxide whisker, 1.5kg of tourmaline powder, 7kg of sulfonated flame-retardant mesoporous silicon, 3kg of graphene oxide, 1.5kg of acrylamide, 0.05kg of potassium permanganate, 1.5kg of polycarboxylic acid water reducer, 1.5kg of sodium gluconate, 1.5kg of polyvinyl alcohol, 1.5kg of foam stabilizer, and 2kg of 30% by mass aqueous hydrogen peroxide solution.
[0043] Sulfonated flame-retardant mesoporous silica was prepared by the following specific operation: 2 kg AEO-9 was added to 30 kg water and stirred evenly, 3 kg ethyl orthosilicate and 1.5 kg aluminum dihydrogen phosphate were added thereto, stirred at a speed of 300 r / min for 7 min, the stirring temperature was 45 ° C, the pH value of the system was adjusted to 8-9 with 7% ammonia water by mass, stirred for 8 h, 0.5 kg 4-ethylbenzenesulfonic acid was added, stirred at a temperature of 155 ° C for 90 min, the stirring pressure was 0.65 MPa, the temperature was reduced to 50 ° C, filtered, the filter cake was washed, and vacuum dried.
[0044] The preparation method of the green high-strength foamed gypsum comprises the following steps: S1, mixing sulfonated flame retardant mesoporous silica with desulfurized gypsum, PO52.5 silicate cement, nano zinc oxide whiskers, tourmaline powder and foam stabilizer, and stirring at a speed of 150 r / min for 2 min to obtain a premix; S2, adding graphene oxide to 10kg water, ultrasonic dispersion for 8min, ultrasonic frequency of 8kHz, adding acrylamide, continuing ultrasonication for 7min, nitrogen purging for 8min, sealing and sending to cobalt-60 irradiation chamber for irradiation, irradiation dose of 25kGy, irradiation dose rate of 2.94kGy / h, filtering, washing with deionized water twice, vacuum drying; then adding to 40kg water with polycarboxylate water reducer, sodium gluconate, polyvinyl alcohol, potassium permanganate, stirring at a speed of 150r / min for 2min, to obtain a composite admixture; S3. Add the composite admixture to the premix, stir at a speed of 150r / min for 2min, add the hydrogen peroxide aqueous solution, continue stirring for 8s, pour into the mold for foaming, demould after molding for 3h, and cure.
[0045] Comparative Example 1 A green high-strength foamed gypsum, whose raw materials include: 45kg of desulfurized gypsum, 10kg of PO52.5 silicate cement, 1.5kg of nano zinc oxide whisker, 1.5kg of tourmaline powder, 7kg of sulfonated flame-retardant mesoporous silicon, 3kg of graphene oxide, 1.5kg of acrylamide, 0.05kg of potassium permanganate, 1.5kg of polycarboxylic acid water reducer, 1.5kg of sodium gluconate, 1.5kg of polyvinyl alcohol, 1.5kg of foam stabilizer, and 2kg of 30% by mass aqueous hydrogen peroxide solution.
[0046] Sulfonated flame-retardant mesoporous silica was prepared by the following specific operation: 2 kg AEO-9 was added to 30 kg water and stirred evenly, 3 kg ethyl orthosilicate and 1.5 kg aluminum dihydrogen phosphate were added thereto, and the mixture was stirred at a speed of 300 r / min for 7 min, and the stirring temperature was 45 ° C. The pH value of the system was adjusted to 8-9 with 7% ammonia water by mass, and the mixture was stirred for 8 h, filtered, the filter cake was washed, and vacuum dried.
[0047] The preparation method of the green high-strength foamed gypsum comprises the following steps: S1, mixing sulfonated flame retardant mesoporous silica with desulfurized gypsum, PO52.5 silicate cement, nano zinc oxide whiskers, tourmaline powder and foam stabilizer, and stirring at a speed of 150 r / min for 2 min to obtain a premix; S2, adding graphene oxide to 10kg water, ultrasonic dispersion for 8min, ultrasonic frequency of 8kHz, adding acrylamide, continuing ultrasonication for 7min, nitrogen purging for 8min, sealing and sending to cobalt-60 irradiation chamber for irradiation, irradiation dose of 25kGy, irradiation dose rate of 2.94kGy / h, filtering, washing with deionized water twice, vacuum drying; then adding to 40kg water with polycarboxylate water reducer, sodium gluconate, polyvinyl alcohol, potassium permanganate, stirring at a speed of 150r / min for 2min, to obtain a composite admixture; S3. Add the composite admixture to the premix, stir at a speed of 150r / min for 2min, add the hydrogen peroxide aqueous solution, continue stirring for 8s, pour into the mold for foaming, demould after molding for 3h, and cure.
[0048] Comparative Example 2 A green high-strength foamed gypsum, whose raw materials include: 45kg of desulfurized gypsum, 10kg of PO52.5 silicate cement, 1.5kg of nano zinc oxide whisker, 1.5kg of tourmaline powder, 7kg of sulfonated flame-retardant mesoporous silicon, 3kg of graphene oxide, 0.05kg of potassium permanganate, 1.5kg of polycarboxylic acid water reducer, 1.5kg of sodium gluconate, 1.5kg of polyvinyl alcohol, 1.5kg of foam stabilizer, and 2kg of 30% by mass aqueous hydrogen peroxide solution.
[0049] Sulfonated flame-retardant mesoporous silica was prepared by the following specific operation: 2 kg AEO-9 was added to 30 kg water and stirred evenly, 3 kg ethyl orthosilicate and 1.5 kg aluminum dihydrogen phosphate were added thereto, stirred at a speed of 300 r / min for 7 min, the stirring temperature was 45 ° C, the pH value of the system was adjusted to 8-9 with 7% ammonia water by mass, stirred for 8 h, 0.5 kg 4-ethylbenzenesulfonic acid was added, stirred at a temperature of 155 ° C for 90 min, the stirring pressure was 0.65 MPa, the temperature was reduced to 50 ° C, filtered, the filter cake was washed, and vacuum dried.
[0050] The preparation method of the green high-strength foamed gypsum comprises the following steps: S1, mixing sulfonated flame retardant mesoporous silica with desulfurized gypsum, PO52.5 silicate cement, nano zinc oxide whiskers, tourmaline powder and foam stabilizer, and stirring at a speed of 150 r / min for 2 min to obtain a premix; S2, adding graphene oxide, polycarboxylate water reducer, sodium gluconate, polyvinyl alcohol and potassium permanganate to 40 kg of water, stirring at a speed of 150 r / min for 2 min to obtain a composite admixture; S3. Add the composite admixture to the premix, stir at a speed of 150r / min for 2min, add the hydrogen peroxide aqueous solution, continue stirring for 8s, pour into the mold for foaming, demould after molding for 3h, and cure.
[0051] The performance tests of the foamed gypsum obtained in Example 5 and Comparative Examples 1-2 are as follows: 1. Refer to GB / T8624-2012 "Combustion Performance Classification of Building Materials and Products" to measure the combustion performance level of the sample.
[0052] The combustion performance grade of the foamed gypsum obtained in Example 5 and Comparative Examples 1-2 is both A1.
[0053] 2. Refer to GB / T18696.2-2002 "Measurement of sound absorption coefficient and acoustic impedance in acoustic impedance tubes Part 2: Transfer function method" to measure the noise reduction coefficient of the sample. The noise reduction coefficient is taken as the average value of the sound absorption coefficient at frequencies of 125Hz, 250Hz, 500Hz, 1000Hz, and 2000Hz. Refer to GB / T 17671-2021 "Test method for strength of cement mortar (ISO method)" to test the compressive strength and flexural strength of the sample.
[0054] like Figure 1 and Figure 2 As shown, the foamed gypsum obtained in Example 5 has a small bulk density, high noise reduction coefficient, compressive strength and flexural strength, all of which are better than those of Comparative Examples 1-2 (P < 0.05), indicating that the foamed gypsum obtained in Example 5 has a good foaming effect and can effectively enhance the compressive and flexural strengths.
[0055] 3. Refer to GB / T 10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Heat Flow Meter Method" to measure the thermal conductivity of the sample; refer to GB / T 29417-2012 "Test method for drying shrinkage and cracking properties of cement mortar and concrete" to measure the drying shrinkage rate of the sample.
[0056] like Figure 3 As shown, the thermal conductivity and drying shrinkage of the foamed gypsum obtained in Example 5 and Comparative Example 1 are relatively small, and there is no significant difference between the two (P>0.05); but both groups are better than Comparative Example 2 (P<0.05).
[0057] 4. Refer to GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" to measure the permeability coefficient of the sample after different freeze-thaw cycles.
[0058] like Figure 4 As shown, the permeability coefficients of the foamed gypsum obtained in Example 5 and Comparative Example 1 are always low, while the permeability coefficient of the foamed gypsum obtained in Comparative Example 2 increases significantly with the increase in the number of freeze-thaw cycles.
[0059] This is because the present invention uses fatty alcohol polyoxyethylene ether as a mesoporous template, tetraethyl orthosilicate as a precursor, and is compounded with aluminum dihydrogen phosphate to obtain a flame-retardant mesoporous silicon material, which can effectively improve the heat resistance and flame retardancy. The surface of the flame-retardant mesoporous silicon material is then sulfonated, which can combine with the surface amino groups of grafted graphene oxide in the composite admixture to form a dense body of a gel structure, thereby improving the flexural strength of the system, reducing shrinkage, and preventing structural cracking. At the same time, a three-dimensional cross-linking effect is generated, which forms a dense colloidal structure together with fine gypsum particles. The structure not only has high hardness, but also can effectively block water infiltration and has excellent freeze-thaw resistance, that is, the freeze-thaw cycle has no effect on its anti-seepage properties. The invention is irradiated to graft acrylamide onto graphene oxide, so that the graphene oxide has an amphiphilic property and can effectively promote the uniform dispersion of additives such as water reducer, retarder, thickener, potassium permanganate, etc. into the premix. The grafted graphene oxide is combined with nano whiskers to effectively promote the uniform dispersion of chemical foaming agent in the system and promote the stable generation of foam, thereby generating fine foam, forming a uniform foamed gypsum board, and enhancing the strength of the hardened body.
[0060] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A green high-strength foamed gypsum, characterized in that: The raw materials include, by mass: 30-60 parts of gypsum, 5-15 parts of cement, 1-2 parts of nano whiskers, 1-2 parts of tourmaline powder, 4-10 parts of sulfonated flame-retardant mesoporous silicon, 1-5 parts of graphene oxide, 1-2 parts of acrylamide, 0.01-0.1 parts of potassium permanganate, 1-2 parts of water reducer, 1-2 parts of retarder, 1-2 parts of thickener, 1-2 parts of foam stabilizer, and 1-3 parts of chemical foaming agent; Sulfonated flame-retardant mesoporous silica uses fatty alcohol polyoxyethylene ether as a mesoporous template, tetraethyl orthosilicate as a precursor and is compounded with aluminum dihydrogen phosphate, and then is obtained by sulfonation treatment.
2. The green high-strength foamed gypsum according to claim 1, characterized in that: The gypsum is desulfurized gypsum; the cement is PO52.5 silicate cement.
3. The green high-strength foamed gypsum according to claim 1, characterized in that: The nano whisker is at least one of nano zinc oxide, nano tin oxide and nano zinc hydroxy stannate.
4. The green high-strength foamed gypsum according to claim 1, characterized in that: The water reducer is a naphthalene-based water reducer or a polycarboxylic acid water reducer; the thickener is hydroxypropyl methylcellulose or / and polyvinyl alcohol.
5. The green high-strength foamed gypsum according to claim 1, characterized in that: The chemical blowing agent is aqueous hydrogen peroxide solution.
6. The green high-strength foamed gypsum according to claim 1, characterized in that: Sulfonated flame-retardant mesoporous silica is prepared by the following specific operation: add fatty alcohol polyoxyethylene ether into water and stir evenly, add tetraethyl orthosilicate and aluminum dihydrogen phosphate thereto, stir at 40-50°C for 5-10 minutes, adjust the pH value of the system to 8-9, stir for 5-10 hours, add 4-ethylbenzenesulfonic acid, stir at 150-160°C for 1-2 hours, cool to 40-60°C, filter, wash the filter cake, and vacuum dry.
7. The green high-strength foamed gypsum according to claim 6, characterized in that: The mass ratio of fatty alcohol polyoxyethylene ether, ethyl orthosilicate, aluminum dihydrogen phosphate and 4-ethylbenzenesulfonic acid is 1-3:2-4:1-2:0.1-1.
8. A method for preparing the green high-strength foamed gypsum according to any one of claims 1 to 7, characterized in that: The steps include: S1. Stirring sulfonated flame-retardant mesoporous silica with gypsum, cement, nano whiskers, tourmaline powder and foam stabilizer for 1-3 minutes to obtain a premix; S2, adding graphene oxide to water, ultrasonically dispersing for 5-10 minutes, adding acrylamide and continuing ultrasonication for 5-10 minutes, purging with nitrogen for 5-10 minutes, sealing and irradiating with cobalt-60, the irradiation dose is 20-30 kGy, filtering, washing with water, and vacuum drying; then adding water reducer, retarder, thickener, and potassium permanganate to water and stirring for 1-3 minutes to obtain a composite admixture; S3. Add the composite admixture to the premix and stir for 1-3 minutes. Add the chemical foaming agent and continue stirring for 5-10 seconds. Pour, foam, and mold for 2-4 hours before demoulding and curing.
9. The method for preparing green high-strength foamed gypsum according to claim 8, characterized in that: In S2, the ultrasound frequency is 5-10kHz.
10. The method for preparing green high-strength foamed gypsum according to claim 8, characterized in that: In S2, the irradiation dose rate was 2.9-3.0 kGy / h.
Citation Information
Patent Citations
Polymer grafted graphene oxide and preparation method thereof
CN102731733A
Mesoporous flame-retardant grafted graphene material and preparation method thereof
CN106832411A
Graphene modified foamed plaster sound-absorbing material and preparation method thereof
CN107673776A
Reinforcing agent for foam cement, and foam cement using same
CN111187018A